Cattle helminth infections in England and Wales: an investigation into prevalence, risk factors, attitudes and impacts - Bellet, Camille Sylvie Charlotte (2017)
Worldwide, there is an increasing demand for food, especially meat and milk. Alongside concerns around sustainability and other issues such as animal welfare, high expectations are put on livestock systems for an increased production and efficiency in order to meet such a demand. Helminth infections are ubiquitous on cattle farms and represent a growing concern for the industry around the world. In the UK, Ostertagia ostertagi and Fasciola hepatica are recognised as parasites of major importance in terms of their economic impact on cattle production and animal welfare. Rumen fluke is another strong candidate in the list of helminths which represent challenges for the sector in the UK. However, because helminth infections are mainly subclinical, their control is often very difficult. In this context, farmers generally adopt blanket treatment in young-stock to prevent or regain production losses due to these infections. This results in increasing problems of helminth resistance to available drugs, making such a practice unsustainable. Motivated by these concerns, several guidelines for best-practice on cattle helminth control have been published in the past few years. Nonetheless, farmers’ have been reluctant to adopt the recommendations put forward by these documents.